2015
DOI: 10.1259/bjr.20140436
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis of the subaxial cervical spine following treatment for head and neck carcinomas

Abstract: Objective: To study MRI and positron emission tomography (PET)/CT imaging of osteoradionecrosis (ORN) of the subaxial cervical spine, a serious long-term complication of radiation therapy (RT) for head and neck cancers that can lead to pain, vertebral instability, myelopathy and cord compression. Methods: This is a single-institution retrospective review of patients diagnosed and treated for ORN of the subaxial cervical spine following surgery and radiation for head and neck cancer. Results: We report PET/CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Recently, MRI has been recommended as a very useful technique for the identi cation of benign and malignant vertebral diseases [32,33]. There are several studies have clari ed the value of MRI for diagnosis of ORN, displayed that cervical spine ORN could be misdiagnosed as bone metastasis, because cervical ORN could show soft-tissue masses and present abnormal enhancement [6,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MRI has been recommended as a very useful technique for the identi cation of benign and malignant vertebral diseases [32,33]. There are several studies have clari ed the value of MRI for diagnosis of ORN, displayed that cervical spine ORN could be misdiagnosed as bone metastasis, because cervical ORN could show soft-tissue masses and present abnormal enhancement [6,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multicenter validation is needed to achieve strong evidence for its clinical application. Second, as described in previous studies [6,9,10], pathologic con rmation for cervical spine ORN and bone metastasis was not available attributed to the relatively high risks related to biopsy of the cervical spine (eg, injury to the vertebral artery or the cervical spinal cord). Third, only radiomics features are selected to construct a nomogram model, because the object of this study was cervical spine lesion, considering the fact that patients could involve single or multiple lesions, include patients' clinical factors could create selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Since osteomyelitis and osteodiscitis are proposed to represent infectious complications of underlying ORN [16], patient 1 possibly initially suffered from this.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review revealed 1 case presented by Ekbom et al 2 of a 56-year-old woman with a history of laryngeal cancer postradiation, esophageal dilation, and neck pain, who had negative findings on computed tomography examination, and was later diagnosed with osteomyelitis on magnetic resonance imaging. Magnetic resonance imaging has the highest specificity in diagnosing cervical osteomyelitis 5 ; however, the indications and timing of imaging for this patient population are not clear.…”
Section: To the Editormentioning
confidence: 99%